Antibiotics utilization patterns among tertiary care hospitals in Ethiopia - Abebe Kebede; Kifle Woldemichael; Dereje Kebede; Sileshi Dubale; Wendossen Shewarega; Alemseged Beyene Berha; Sultan Suleman (PLoS ONE, 2025)
Background Antibiotics are among the most used medicines globally, but antimicrobial resistance (AMR) threatens their effectiveness. The greatest mortality burden associated with AMR is in sub-Saharan Africa. However, antimicrobial prescribing practice and stewardship remain challenges in the African regions. Thus, this study aimed to evaluate and compare antibiotic utilization patterns in tertiary hospitals in Ethiopia during 2022. Method A retrospective cross-sectional study was conducted in adult wards of five public tertiary care hospitals in Ethiopia with a total of 3,283 beds. Data were retrieved from 807 randomly selected patient records using the online Kobo tool. Analysis utilized the World Health Organization (WHO) Anatomical Therapeutic Chemical (ATC) classification system and the Defined Daily Dose (DDD) (ATC/DDD) method. The result was presented using tables, charts, and text. Results A total of 2,718 drugs were prescribed to 807 patients with an average of 3.4 drugs per patient (range 1–7) during a total of 8638 bed-days. Of the total drugs prescribed, antibiotics account for 1,035 (38%), with an average of 1.3 (1,035/807) antibiotics per patient. Five hundred fifty-six (69%) patients were prescribed at least one antibiotic. The overall antibiotic consumption was 108 DDD/100 bed-days, 37.5/100 bed-days for hospital-acquired infections, and 32.8/100 bed-days for community-acquired infections. The rest were for prophylaxis purposes. The majority of antibiotics were prescribed in medical and surgical wards; 34.9/100 and 27.5/100 bed-days, respectively. The most prescribed antibiotics were ceftriaxone, metronidazole, and ceftazidime. Overall, the AWaRe “Watch” group antibiotics use occurred in 74% (73 DDD/100 bed-days) of total antibiotic consumption, which was higher than the WHO recommendation (at least 60% of total antibiotic use should be from the “Access” group, not the “Watch” group). Conclusion Antibiotic use was high in Ethiopian tertiary hospitals, with most patients receiving antibiotics, mainly from the WHO “Watch” group, contrary to guidelines. Three classes (cephalosporins, imidazoles, and glycopeptides) made up the majority of prescriptions, mostly for hospital-acquired infections. Urgent interventions and strengthened antimicrobial stewardship are needed to address inappropriate use and combat resistance.